Electrodeposition mechanism and corrosion behavior of multilayer nanocrystalline nickel-tungsten alloy. (20th December 2017) - Allahyarzadeh, M.H.; Aliofkhazraei, M.; Rouhaghdam, A. Sabour; Torabinejad, V.; Alimadadi, H.; Ashrafi, A.
Abstract: Multilayer nickel-tungsten coatings were deposited on carbon steel using the pulse reverse current technique. Nickel-tungsten layered structure coatings were developed using the continuous and alternative variation of pulse duty cycle at two specific and fixed values. In these coatings, the multilayer structure is composed of two nickel-tungsten layers with alternating chemical compositions of 25 wt%W and 11 wt%W. Dynamic electrochemical impedance spectroscopy (DEIS) revealed three time constants in the electrical equivalent circuit corresponding to the electrodeposition mechanism of nickel-tungsten. In order to evaluate the electrochemical behavior of the multilayer structure, the investigation of the multilayer coatings was carried out via cyclic potentiodynamic polarization, in a sulfuric acid media which contained chloride ions. Cyclic voltammetry test was introduced and subsequently employed as a novel electrochemical evaluation for layered structures. Morphological, elemental and Raman analysis were carried out. Analyzing the surface products revealed that nickel tends to dissolve in presence of tungsten, and even more in an electrolyte containing chloride ions. It was also revealed that the diffusive species of the electrolyte encountered a larger interface in multilayer structures. Hence, they spread out along and throughout the active layers; which significantly delays the penetration towards the substrate. Enhanced service life of the noble layers is achieved owing to the galvanic effect. According to the findings, these kinds of coatings are more resistant to localized attack in comparison to monolithic coatings. Graphical abstract: